Viral and bacterial lung infections in children: algorithms for diagnosis and therapy. A review - Alexander B. Malakhov; Alena Iu. Sedova; Natalia G. Kolosova; Pavel V. Berezhanskiy; Tatiana A. Gutyrchik (Consilium Medicum, 2023)
Community-acquired pneumonia is among the most common lower respiratory infections. The main etiological factors of lower respiratory infections are bacteria, viruses, and combinations. Pediatricians are increasingly faced with the problem of treating patients with infections caused by multidrug-resistant bacteria and viral lung infections; therefore, differential diagnosis of viral and bacterial lung infections in children is relevant. Significant progress has been made in diagnosing, treating, and preventing pneumonia in children; however, some issues require improvement in approaches to the differential diagnosis of lung infections in children. The paper aims to familiarize healthcare providers with modern principles of differential diagnosis and treatment of lung infections in children.